Non-carcinogenic health risks of heavy metal in mudfish from Laguna Lake - Molina, Victorio B. (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
This paper examines the potential risks to human health associated with exposure to heavy metal that have bioaccumulated in Mudfish (Ophicephalus striatus) from Laguna Lake. Fish samples were collected in eight sampling stations in three major areas of the lake during the dry and wet seasons. Dry season samples were collected from May to June 2010 and wet season samples, from September to November 2010. Coordinates of sampling site locations were recorded using Global Positioning System (GPS) and plotted in Geographic Information System (GIS) digital maps. Heavy metal analyses for cadmium (Cd), lead (Pb), mercury (Hg), arsenic (As), and chromium (Cr) were conducted using Atomic Absorption Spectrophotometer (AAS) and a Mercury Analyzer (Mercur-Duo). Estimates of health risks associated with mudfish consumption were summarized according to non-carcinogenic effects. Non-carcinogenic Hazard Quotient (NHQ) values of five heavy metal showed that lead is the most urgent pollutant of concern in terms of adverse health effects from risks associated with mudfish consumption from all sampling locations in the lake. From the point of view of human health protection and disease prevention, mudfish from Laguna Lake is not fit for long-term human consumption primarily due to lead and mercury contamination. Keywords: Bioaccumulation, health risk assessment, heavy metal, Laguna Lake, mudfish